Long stay institutions for the elderly and covid-19: Emergency in the debate (Research, Society and Development, 2020)
Introduction: COVID-19 is a disease that has as one of its characteristics to reach more aggressively the elderly and people with chronic diseases. Objective: to present a brief reflection on the urgency of the debate in relation to Long Term Care Institutions for the Elderly and COVID-19. Methodology: Descriptive, reflective study, based on a critical reading about the disease and its possible impacts on Long Term Care Institutions for the Elderly. For data collection, a bibliographic search was carried out on Google Scholar on the subject. Results: The demands brought by the COVID-19 infection, despite requiring innovative methods of intervention, reaffirm the importance of the Health Pact, in relation to comprehensive care for the elderly. As one of the coping strategies for this pandemic by elderly institutions, it is proposed to build contingency plans that consider the specificities of these spaces as a place of collective coexistence and the different demands of its residents. Conclusion: reflections on the urgency in the debate about these instituicions as vulnerable spaces to the pandemic of COVID-19, pondered the diversity that exists in these places with regard to residents, physical structure and the capacity of professionals to care, based on the specificities of the aging to avoid being affected by a drama that would mark them as the epicenter of necropolitics.